2013
DOI: 10.1121/1.4768792
|View full text |Cite
|
Sign up to set email alerts
|

Merging physical parameters and laboratory subjective ratings for the soundscape assessment of urban squares

Abstract: An experimental study was carried out in 20 squares in the center of Rome, covering a wide range of different uses, sonic environments, geometry, and architectural styles. Soundwalks along the perimeter of each square were performed during daylight and weekdays taking binaural and video recordings, as well as spot measurements of illuminance. The cluster analysis performed on the physical parameters, not only acoustic, provided two clusters that are in satisfactory agreement with the "a priori" classification.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 15 publications
0
22
0
Order By: Relevance
“…Many researchers have investigated the effects of environmental context including visual images, fragrances, and daylight on soundscape perception. It was found that visual environment was significantly related to soundscapes (Flindell and Stallen, 1999;Job and Hatfield, 2001;Carles et al, 1992;Viollon et al, 2002;Jeon et al, 2011;Brambilla et al, 2013b;Jeon et al, 2013).…”
Section: Introductionmentioning
confidence: 93%
“…Many researchers have investigated the effects of environmental context including visual images, fragrances, and daylight on soundscape perception. It was found that visual environment was significantly related to soundscapes (Flindell and Stallen, 1999;Job and Hatfield, 2001;Carles et al, 1992;Viollon et al, 2002;Jeon et al, 2011;Brambilla et al, 2013b;Jeon et al, 2013).…”
Section: Introductionmentioning
confidence: 93%
“…Although processes of globalization and new technologies can change the urban soundscape making its recognition harder, this intangible element does not always lose its intrinsic characteristics as recognized and felt by the population and it becomes one of the signs of the identity of a city (Maffei, Iannace, & Lembo, 2004;Brambilla, De Gregorio, Maffei, Yuksel Can, & Ozcevik, 2007;Gómez Escobar, et al, 2012;Brambilla, Maffei, Di Gabriele, & Gallo, 2013).…”
Section: How Are Soundscapes Shaping Our History?mentioning
confidence: 99%
“…[21][22][23][24][25] In this context, the interaction between visual and aural perceptions has become a topic of interest. 13,23,[26][27][28][29] In the research by Carles et al, 26 respondents were required to rate their preference for image, sound, and image-sound combinations, respectively, following a specifically designed process. The results showed that any incongruence between sound and image would diminish landscape preference.…”
mentioning
confidence: 99%